Sports genetics moving forward - lessons learned from medical research - Mattsson, C. M.; Wheeler, M.; Waggott, D.; Caleshu, C. (Physiological Genomics, 2016)
Sports genetics can take advantage of lessons learned from human disease genetics. By righting past mistakes and increasing scientific rigor, the breadth and depth of knowledge in the field can be magnified. We present an outline of challenges facing sports genetics in the light of experiences from medical research.